2023
DOI: 10.1002/cssc.202300460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and H Flux on the NH3 Synthesis via Electrochemical Hydrogen Permeation

Abstract: Ammonia is an indispensable commodity and a potential carbon free energy carrier. The use of H permeable electrodes to synthesize ammonia from N 2 , water and electricity, provides a promising alternative to the fossil fuel based Haber-Bosch process. Here, H permeable Ni electrodes are investigated in the operating temperature range 25-120 °C, and varying the rate of electrochemical atomic hydrogen permeation. At 120 °C, a steady reaction is achieved for over 12 h with 10 times higher cumulative NH 3 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Although the rate of ammonia generation by this approach is very small compared to the liquid‐phase reduction, assuming the absence of false‐positive in the liquid‐phase reduction, this unconventional approach involves interesting chemistry and is in the nascent stage. In a very recent publication, the authors have demonstrated a 40‐fold enhancement in the FE and improved ammonia generation (10 times higher) at 120 °C with a cell potential of 1.4 V (6.6 kWh kg −1 ammonia) [121] …”
Section: Electrolyte Engineeringmentioning
confidence: 99%
“…Although the rate of ammonia generation by this approach is very small compared to the liquid‐phase reduction, assuming the absence of false‐positive in the liquid‐phase reduction, this unconventional approach involves interesting chemistry and is in the nascent stage. In a very recent publication, the authors have demonstrated a 40‐fold enhancement in the FE and improved ammonia generation (10 times higher) at 120 °C with a cell potential of 1.4 V (6.6 kWh kg −1 ammonia) [121] …”
Section: Electrolyte Engineeringmentioning
confidence: 99%